2020
DOI: 10.3892/or.2020.7751
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑216a‑5p suppresses esophageal squamous cell carcinoma progression by targeting KIAA0101

Abstract: The KIAA0101 protein (also referred to as NS5ATP9 or Paf15) is overexpressed in esophageal squamous cell carcinoma (ESCC) and is associated with disease progression and poor patient survival, but how KIAA0101 expression is regulated remains unknown. The relationship between tumor miR-216a-5p expression and prognosis in patients with ESCC was revealed by survival analyses. Quantitative reverse-transcriptase PCR and western blot analysis were used to evaluate miR-216a-5p and KIAA0101 expression in human ESCC tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
(58 reference statements)
2
9
0
Order By: Relevance
“…Studies in recent years have revealed that PCLAF is overexpressed in several types of GI tract tumors, including esophageal cancer[ 6 , 7 ], GC[ 8 - 10 ], and CRC[ 39 , 43 ]. Some studies have also shown a strong association between PCLAF and tumors in accessory organs of digestion, including PC[ 15 ] and liver cancer[ 12 - 14 , 44 - 46 ].…”
Section: Pclaf Contributes To the Development Of Gi Tumorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies in recent years have revealed that PCLAF is overexpressed in several types of GI tract tumors, including esophageal cancer[ 6 , 7 ], GC[ 8 - 10 ], and CRC[ 39 , 43 ]. Some studies have also shown a strong association between PCLAF and tumors in accessory organs of digestion, including PC[ 15 ] and liver cancer[ 12 - 14 , 44 - 46 ].…”
Section: Pclaf Contributes To the Development Of Gi Tumorsmentioning
confidence: 99%
“…Knockdown of PCLAF increases cell numbers in the G1 phase by flow cytometry analysis, and downregulates the protein levels of cyclin A and B, indicating that PCLAF might control esophageal cancer cell viability via induction of cyclin A and B[ 7 ]. PCLAF also promoted cell migration and invasion in ESCC EC9706 and TE1 cell lines using the transwell assay[ 6 ]. Moreover, elevated PCLAF expression predicts a worse response to chemotherapy.…”
Section: Pclaf Contributes To the Development Of Gi Tumorsmentioning
confidence: 99%
See 3 more Smart Citations